Achieving Business Sustainability Through Managing Generations Z Turnover Intention - Cahyadi, Claudia; Putrilestari, Rianti; Luthfiah Effendi, Salsabila; Maharani, Anita (Jurnal Manajemen, 2024)
This study aimed to determine the effect of employer brand equity, employment development system, and work environment towards job satisfaction which affects employee turnover intention. This research used a quantitative approach method, and the sample was taken by using a convenient sampling method with individuals as the unit of analysis who are Generation Z with birth years above 1997 and who already have work activities in the city of Jakarta and its surroundings. Data collection had done online using Google Forms and resulted in 253 responses that could be used. The result showed that all of the hypotheses were rejected. The result obtained from this study are expected to benefit company management in analyzing and mapping the level of job satisfaction, workplace spirituality, and organizational citizenship behaviour for employee performance.